A Cases Report of 55-Year-Old Lady with Recurrent Seizure with History of Thyroidectomy (Journal of National Institute of Neurosciences Bangladesh, 2022)
Permanent hypoparathyroidism is not uncommon following thyroidectomy. However, hypoparathyroidism can present with neurological features like seizures, paresthesia, depression, psychosis, extrapyramidal manifestations and features of raised intracranial pressure. Here we present a case of recurrent seizure with history of thyroidectomy 10 years back. The patient was clinically and biochemically hypocalcaemic due to hypoparathyroidism and her brain imaging shows diffuse intracranial calcification. Patient was managed with anticonvulsant, calcium gluconate, calcitriol and levothyroxine. Chronic hypocalcaemia due to postoperative hypoparathyroidism can cause diffuse intracranial calcification which in turn triggers several neurological symptoms like seizure. Therefore judicial surgery and regular post-operative follow up is required to prevent such complications.Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):100-102